Delivery of Toxins and Effectors by Bacterial Membrane Vesicles - Adrian Macion; Agnieszka Wyszyńska; Renata Godlewska (Toxins, 2021)
Pathogenic bacteria interact with cells of their host via many factors. The surface components, i.e., adhesins, lipoproteins, LPS and glycoconjugates, are particularly important in the initial stages of colonization. They enable adhesion and multiplication, as well as the formation of biofilms. In contrast, virulence factors such as invasins and toxins act quickly to damage host cells, causing tissue destruction and, consequently, organ dysfunction. These proteins must be exported from the bacterium and delivered to the host cell in order to function effectively. Bacteria have developed a number of one- and two-step secretion systems to transport their proteins to target cells. Recently, several authors have postulated the existence of another transport system (sometimes called “secretion system type zero”), which utilizes extracellular structures, namely membrane vesicles (MVs). This review examines the role of MVs as transporters of virulence factors and the interaction of toxin-containing vesicles and other protein effectors with different human cell types. We focus on the unique ability of vesicles to cross the blood–brain barrier and deliver protein effectors from intestinal or oral bacteria to the central nervous system.